The interactions between human antithrombin and heparin - Chen, Ye Wu Iris (My University, 1997)
Antithrombin is a plasma serine proteinase inhibitor functioning physiologically as an anticoagulant. It inactivates thrombin and FXa by forming a 1:1 covalent complex between its P1 Arg and the catalytic serine of the proteinase. Antithrombin is a relatively inefficient inhibitor until it is activated by two specific glycosaminoglycans, heparin and heparan sulphate with the unique pentasaccharide sequence required for high affinity binding to antithrombin. Activation of antithrombin by the pentasaccharide and full-length heparin induces major conformational changes in the antithrombin molecule. The pentasaccharide binding site of antithrombin has been mapped to the D-helix, the A-helix, and the N-terminus of the molecule. Arg47 is located where the base of the A-helix is in close proximity to the amino end of the D-helix. To characterize the role of Arg47 in antithrombin binding to and its activation by the pentasaccharide, antithrombin moieties with substitutions at Arg47 were created and expressed in transfected COS-1 cells. Our data suggest that a positively charged amino acid at position 47 is essential for heparin and the pentasaccharide to bind to AT with high affinity and the pentasaccharide- and heparin-accelerated inactivation of FXa. In addition, an Arg is preferred to Lys for activation by the pentasaccharide with respect to FXa inhibition. Antithrombin interacts with target proteinases primarily through its P1-P1' residues together with flanking binding subsites in the reactive centre loop. Heparin activates antithrombin through inducing a major conformational change in antithrombin which optimizes the presentation of the reactive centre loop to the target proteinases. While the pentasaccharide is sufficient for enhancing the rate of FXa inhibition, it has little effect on thrombin inactivation. Full-length heparin, on the other hand, enhances the rates of antithrombin inhibition of both FXa and thrombin. As demonstrated by the coincident 40% increase in endogenous Trp fluorescence with plasma antithrombin, the pentasaccharide and full-length heparin were reported to induce similar conformational changes in AT. The large rate enhancement of thrombin inhibition by full-length heparin was thus attributed solely to the ability of longer chains to accommodate AT and thrombin simultaneously. Based on the fact that substrate recognition of thrombin and FXa is different, it was hypothesized that the pentasaccharide and full-length heparin induce different reactive centre loop conformations. A Pro397Trp antithrombin moiety thus was generated in transfected CHO cells. We report here, for the first time, that the pentasaccharide and full-length heparin induce different conformational changes in the reactive centre loop. It thus appears that the pentasaccharide-induced reactive centre loop conformation represents a near optimal substrate to FXa, whereas the heparin-induced RCL conformation is apparently required for near optimal interaction with thrombin.
Keywords: science